La violence physique et la maltraitance affective dans les fréquentations chez un groupe d'adolescent(e)s - Gagné, Marie-Hélène; Lavoie, Francine (Canadian Journal of Counselling and Psychotherapy, 2007)
This study explores the extent of the phenomenon of physical violence and emotional mal treatment in adolescent's dating relationships. One hundred and one youths from a private secondary school answered a questionaire concerning violence which they sustained and inflicted in this context. Results show a prevalence of emotional maltreatment among these adolescents though physical violence is also present in their intimate relationships. Gender differences were observed in physical violence but not in emotional maltreatment. However these results must be interpreted with care, since this questionaire failed to consider the context of the violent acts. Suggestions are made for future studies, especially in order to facilitate gender comparisons.